FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT KECACINGAN PADA ANAK SEKOLAH DASAR DI KELURAHAN LEGOK KOTA JAMBI TAHUN 2020 - Silvia Dita; Eti Kurniawati (LLDIKTI Wilayah X, 2021)
Ascariasis is a public health problem that still widespread throughout in the world. This research is an analytical research with a cross-sectional design. The research was conducted on 3 June-3 July 2020 at the Legok Village. The sample this study were children aged 6-10 years, totaly 90 people who were taken by cluster random sampling. Data analysis used chi square statistical test.The results of the study were obtained from 90 respondents whose feces were examined at the Laboratory of the Pusekesmas Putri Ayu. It was known that as many 14 (15.6%) respondents were infected by Ascariasis and 76 (84.4%) respondents weren’t infected by Ascariasis. There is a significant relationship between personal hygiene (p-value = 0.001), there is a significant relationship between the availability of latrines (p-value = 0.000), there is a significant relationship between the availability of clean water facilities (p-value = 0.000), there is no relationship meaning between floor of the house (p-value = 0.046) and there is no significant relationship between parental attention (p-value = 0.033) with the incidence of worms in elementary school-aged children in Legok Village, Jambi City in 2020. It is advisable for children to maintain personal hygiene, Kelurahan Legok to build communal latrines and clean water facilities. Meanwhile, Putri Ayu Community Health Center provides education to parents about the dangers of worms in children